Place cells in the hippocampus: eleven maps for eleven rooms - Alme, Charlotte B; Miao, Chenglin; Jezek, Karel; Treves, Alessandro; Moser, Edvard I; Moser, May-Britt (Proceedings of the National Academy of Sciences of the United States of America, 2014)
The contribution of hippocampal circuits to high-capacity episodic memory is often attributed to the large number of orthogonal activity patterns that may be stored in these networks. Evidence for high-capacity storage in the hippocampus is missing, however. When animals are tested in pairs of environments, different combinations of place cells are recruited, consistent with the notion of independent representations. However, the extent to which representations remain independent across larger numbers of environments has not been determined. To investigate whether spatial firing patterns recur when animals are exposed to multiple environments, we tested rats in 11 recording boxes, each in a different room, allowing for 55 comparisons of place maps in each animal. In each environment, activity was recorded from neuronal ensembles in hippocampal area CA3, with an average of 30 active cells per animal. Representations were highly correlated between repeated tests in the same room but remained orthogonal across all combinations of different rooms, with minimal overlap in the active cell samples from each environment. A low proportion of cells had activity in many rooms but the firing locations of these cells were completely uncorrelated. Taken together, the results suggest that the number of independent spatial representations stored in hippocampal area CA3 is large, with minimal recurrence of spatial firing patterns across environments.
Keywords: hippocampus; Male; Rats; memory; mapování mozku; Brain Mapping; chování zvířat; potkani Long-Evans; place cells; space; nervová síť; Animals; CA3 Region, Hippocampal; zvířata; mužské pohlaví; Behavior, Animal; krysa rodu Rattus; hipokampální oblast CA3; Nerve Net; Rats, Long-Evans